Peran Sekolah Rakyat dalam Pemerataan Akses Pendidikan bagi Keluarga Berpenghasilan Rendah di Kabupaten Jember: Sebuah Studi Kualitatif - Samhadi, Lisa Kartika Rahmawati; Daryono, Daryono; Firmansyah, M. Bayu (Education Journal : Journal Educational Research and Development, 2026)
This qualitative study aims to examine the role of the People's School (Sekolah Rakyat) in expanding access to education for children from low-income families in Jember Regency. Despite government efforts to achieve educational equality, socioeconomic disparities remain a significant barrier, limiting access to quality education services, particularly for marginalized groups. Through interviews, observations, and document analysis, this study explores how the People's School—a free, community-initiated alternative school—contributes to addressing resource constraints, inadequate infrastructure, and digital exclusion experienced by students from poor families. The results indicate that the People's School plays a significant role in increasing school participation, strengthening students' basic academic skills, and enhancing community involvement in education delivery. Its flexible, community-based learning approach enables the school to respond to the learning needs of students at risk of dropping out and experiencing social marginalization. However, the sustainability of the People's School still faces challenges such as limited funding and infrastructure, and a lack of institutional recognition. These findings underscore the importance of partnerships between the government and communities to strengthen the function of People's Schools as an inclusive educational alternative to encourage social mobility and break the chain of intergenerational poverty. Keywords: community-based education; alternative schools; access to education; low-income families; People's Schools